Screening for hypertension in a public dental clinic: A single-centre cross-sectional study in Australia - Shalinie King; Simone Marschner; Haeri Min; Alice Gibson; Niamh Chapman; Clara K. Chow (PLoS ONE, 2026)
Background Hypertension affects over 1.3 million people globally and markers of poor oral health have been associated with hypertension. Objective This study aimed to determine hypertension awareness, treatment and control, among adults attending a public dental clinic, and explore age-related differences between younger (< 65 years) and older adults (≥ 65 years) including associations between markers of oral health and hypertension. Method This cross-sectional study recruited adults ≥18 years from an Australian public dental clinic between November 2022 and May 2023. Two blood pressure readings were obtained using an automated device and the average used for analyses. Demographic, oral health and medical history details were obtained via survey. Hypertension was defined as a systolic blood pressure (SBP) ≥140 mmHg and/or diastolic blood pressure (DBP) ≥90 mmHg, or being aware (self-reported diagnosis), and treated with anti-hypertensive medication. Results Participants (n = 302) were middle aged (mean 59.9 ± 17.5 years, 51.5% ≥ 65 years, 60.7% female), one third had significant tooth loss (<20 teeth), half required treatment for periodontitis and 52.0% had hypertension (95% CI: 46.2%, 57.7%). Of those with hypertension (n = 157), 82.7% were aware, 76.9% were treated for hypertension, and 56.6% of those treated had controlled blood pressure. Although older adults were more likely than younger adults to have hypertension (74.2% vs 28.1%), younger adults were less likely to be aware and treated (70.7% vs 86.8%, 56.1% vs 86.8%, respectively). Markers of poor oral health were not independently associated with hypertension. Conclusions In this population with a high burden of oral disease, hypertension was common highlighting the importance of opportunistic blood pressure assessment. Dental settings may offer an additional point of contact for identifying individuals with undiagnosed or uncontrolled hypertension, particularly among younger adults with lower awareness.